Post-Dredging Nitrogen Dynamics at the Sediment–Water Interface: The Shallow, Eutrophic Mogan Lake, Turkey - Topçu Akasya; Atlığ Seda (Oceanological and Hydrobiological Studies)
The sedimentation and resuspension of various forms of nitrogen in wetlands determines the direction of the nitrogen dynamics. Mogan Lake, in the Gölbaşı Special Environmental Protection Area, is one of the most important Ramsar-nominated wetlands in Turkey. Lake management applications have been performed by the local managers since 2008, including sediment cleaning activities such as dredging. In this context, the aim was to quantitatively predict the nitrogen dynamics (ammonium and nitrate release/uptake in the positive and/or negative direction) at the sediment–water interface, which has not been addressed in the eutrophication and sediment-related studies conducted to date on the lake in question. Sediment ammonium and nitrate flux were estimated to be between −9.16 and 0.36 µg m−2 d−1 and between −67.2 and 35.16 µg m−2 d−1, respectively. The estimations for sediment nitrogen flux in Mogan Lake did not show a regular seasonal or spatial fluctuation. Our results demonstrate that low nitrogen release levels in Mogan Lake do not pose a threat to its nutrient level. In conclusion, both monitoring and reducing external loading is still the top priority for a long-term recovery of water quality in the process of freshwater ecosystems.